2018
DOI: 10.3390/ani8040055
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Integrated Program of Return-to-Field and Targeted Trap-Neuter-Return on Feline Intake and Euthanasia at a Municipal Animal Shelter

Abstract: Simple SummaryDramatic declines in the number of cats admitted to and euthanized at U.S. shelters have taken place in recent decades. Still, millions of cats, many of them free-roaming, enter shelters each year. At some facilities, as many as 70% of feline admissions are euthanized, and it is estimated that, nationally, up to one million or more cats are euthanized each year. New approaches, including return-to-field (RTF) and targeted trap-neuter-return (TNR) appear to have transformative potential. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 15 publications
8
45
0
Order By: Relevance
“…It is estimated that 70% of feline admissions to animal shelters are euthanized in the U.S. [17]. The euthanasia of healthy cats, equally of stray and feral cats, is forbidden in Germany ( § 1 German Animal Welfare Act) [18] , but it is allowed by law that municipalities can establish population management programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that 70% of feline admissions to animal shelters are euthanized in the U.S. [17]. The euthanasia of healthy cats, equally of stray and feral cats, is forbidden in Germany ( § 1 German Animal Welfare Act) [18] , but it is allowed by law that municipalities can establish population management programs.…”
Section: Discussionmentioning
confidence: 99%
“…The euthanasia of healthy cats, equally of stray and feral cats, is forbidden in Germany ( § 1 German Animal Welfare Act) [18] , but it is allowed by law that municipalities can establish population management programs. To reduce an overpopulation of cats, the trap-neuter-return (TNR) program has been successfully established in many countries [5,17,[19][20]. Different methods of surgical or non-surgical contraception, health control, permanent identification, and return/release programs have been launched and analyzed [7,14,[21][22], Kalz [23] found that the population density decreased if all females of a population were spayed and tomcats stayed uncastrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that population control via TNR is effective in reducing the number of cats and nuisance concerns over time Levy, Isaza & Scott, 2014;Spehar & Wolf, 2018;Swarbrick & Rand, 2018). TNR at the colony level alone has been insufficient in reducing the population of community cats and reducing the number of cats admitted to animal shelter (Spehar & Wolf, 2018). The Korean municipality commissions some local animal hospitals to implement sporadic TNR and pays them about $140 per cat (South Korean Ministry of agriculture, food and rural affairs, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to modify the strategy to sterilize more cats within the limited budget. Several countries have modified the TNR strategy to focus on specific areas with larger feline populations, and implemented intensive sterilization with the goal of expanding TNR programs into surrounding areas (Nutter, 2006;Mendes-de Almeida et al, 2011;Johnson & Cicirelli, 2014;Spehar & Wolf, 2018;Zito et al, 2018). This targeted, high-impact TNR intervention is more effective than sporadic TNR in reducing the community cat population (Kortis, 2014;Levy, Isaza & Scott, 2014;Kilgour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%